2019
DOI: 10.1038/s41418-019-0323-8
|View full text |Cite
|
Sign up to set email alerts
|

Dectin-1-induced RIPK1 and RIPK3 activation protects host against Candida albicans infection

Abstract: Necroptosis is a recently defined type of programmed cell death with the specific signaling cascade of receptor-interacting protein 1 (RIPK1) and RIPK3 complex to activate the executor MLKL. However, the pathophysiological roles of necroptosis are largely unexplored. Here, we report that fungus triggers myeloid cell necroptosis and this type of cell death contributes to host defense against the pathogen infection. Candida albicans as well as its sensor Dectin-1 activation strongly induced necroptosis in myeloi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 47 publications
0
26
0
Order By: Relevance
“…Recently, Cao et al (21) found that C. albicans was able to trigger necroptosis in peritoneal macrophages in the presence of pan-caspase inhibitor z-VAD. They also suggested that fungusinduced necroptosis and inflammation is important for host defense against fungal infection (21).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Cao et al (21) found that C. albicans was able to trigger necroptosis in peritoneal macrophages in the presence of pan-caspase inhibitor z-VAD. They also suggested that fungusinduced necroptosis and inflammation is important for host defense against fungal infection (21).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Cao et al (21) found that C. albicans was able to trigger necroptosis in peritoneal macrophages in the presence of pan-caspase inhibitor z-VAD. They also suggested that fungusinduced necroptosis and inflammation is important for host defense against fungal infection (21). Nevertheless, we demonstrated that C. albicans alone can induce necroptosis in macrophages, and Tsc1 M/N2/2 mice exhibited comparable inflammation but more necroptotic macrophages in the kidney.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Once MLKL has been phosphorylated, it will translocate to the cell membrane forming pores, causing a loss of cell membrane integrity and the release of many inflammatory DAMPs [ 50 ]. Necroptosis has also been shown to be mediated via a number of other receptors, including the death receptors Fas and TRAIL, TLRs, and most recently dectin-1 ( Figure 3 ) [ 52 , 53 ].…”
Section: Necroptosismentioning
confidence: 99%
“…Cite this article as Cold Spring Harb Perspect Biol 2020;12:a036368 less able to clear the Gram-negative bacteria Salmonella typhimurium (Shutinoski et al 2016) and Yersinia pseudotuberculosis (Peterson et al 2017). Inhibition of RIPK1 with Nec-1 has also been shown to increase the susceptibility of mice to the fungus Candida albicans (Cao et al 2019). In other infections, however, activation of RIPK1 appears deleterious to the host.…”
Section: Ripk1 Regulates Cell Death and Inflammationmentioning
confidence: 99%